2015
DOI: 10.3389/fpls.2015.00555
|View full text |Cite
|
Sign up to set email alerts
|

Maize miRNA and target regulation in response to hormone depletion and light exposure during somatic embryogenesis

Abstract: Maize somatic embryogenesis (SE) is induced from the immature zygotic embryo in darkness and under the appropriate hormones' levels. Small RNA expression is reprogrammed and certain miRNAs become particularly enriched during induction while others, characteristic to the zygotic embryo, decrease. To explore the impact of different environmental cues on miRNA regulation in maize SE, we tested specific miRNA abundance and their target gene expression in response to photoperiod and hormone depletion for two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 65 publications
2
53
0
Order By: Relevance
“…Transcriptomic datasets on Zea mays embryogenic cultures have shown that the expression pattern of individual auxin-related miRNAs is dependent on the genotype and the age of a culture [66][67][68]78]. The diversity of the miRNA expression profiles in embryogenic cultures, for example, the up-vs. downregulation of the same miRNA, could reflect the complexity of the miRNA-mediated regulatory pathways that fine-tune the somatic cell transcriptome towards embryogenic development in response to specific endo-and exogenous culture factors.…”
Section: Auxin-related Mirnas Fine-tune the Genetic Network That Contmentioning
confidence: 99%
“…Transcriptomic datasets on Zea mays embryogenic cultures have shown that the expression pattern of individual auxin-related miRNAs is dependent on the genotype and the age of a culture [66][67][68]78]. The diversity of the miRNA expression profiles in embryogenic cultures, for example, the up-vs. downregulation of the same miRNA, could reflect the complexity of the miRNA-mediated regulatory pathways that fine-tune the somatic cell transcriptome towards embryogenic development in response to specific endo-and exogenous culture factors.…”
Section: Auxin-related Mirnas Fine-tune the Genetic Network That Contmentioning
confidence: 99%
“…Recently it was found that the induction process in maize is characterized by an enrichment of small RNA molecules that are involved with SE initiation (Chávez-Hernández et al 2015). Chávez-Hernández et al (2015) investigated the accumulation of certain miRNAs, and their predicted targets, during the SE of maize under different environmental conditions.…”
Section: Maizementioning
confidence: 99%
“…Similar to the widely documented involvement of miRNA molecules in plant development in vivo (Jin et al, 2013), the expression of miRNAs was reported during in vitro induced SE in several plant species including Citrus sinensis, Dimocarpus longan, Gossypium hirsutum, Larix kaempferi, Larix leptolepis, Liriodendron tulipifera × L. chinense, Manihot esculenta , and Zea mays (Zhang et al, 2012, 2014; Li et al, 2013; Lin and Lai, 2013; Yang et al, 2013; Chávez-Hernández et al, 2015; Wu et al, 2015; Lin et al, 2015a,b; Khatabi et al, 2016). Thus, the engagement of miRNAs in the embryogenic transition that is induced in vitro is assumed, although knowledge about the function of the specific miRNA in SE induction is very limited.…”
Section: Introductionmentioning
confidence: 99%